Explaining Corporate Capital Structure: Product Markets, Leases, and Asset Similarity - Rauh, Joshua D.; Sufi, Amir (Review of Finance, 2012)
Abstract Better measurement of the output produced and capital employed by firms substantially improves the ability to explain capital structure variation in the cross section. For every firm, we construct the set of other firms producing the same output using the set of product market competitors listed in the firm’s public Securities and Exchange Commission filings. In addition, we improve measurement of capital structure by explicitly accounting for leased capital. These two steps increase the explanatory power of the average capital structure of other firms producing similar output on a firm’s capital structure by 50% compared to using only the average unadjusted debt ratio of other firms in the same three-digit Standard Industrial Classification (SIC) code. We provide evidence that the large explanatory power of the capital structure of other firms producing similar output is related to the assets used in the production process. Our findings suggest that what a firm produces and the assets used in production are the most important determinants of capital structure in the cross section.